1993
DOI: 10.1016/0014-5793(93)80582-f
|View full text |Cite
|
Sign up to set email alerts
|

The IP3‐sensitive calcium store of HIT cells is located in a surface‐derived vesicle fraction

Abstract: Electron microscopic and biochemical techniques were used to study the cellular localization of the ATP‐dependent, IP3‐sensitive, Ca2+ store in the glucose‐ and phosphatidylinositol(PI) agonist‐sensitive hamster insulinoma cell line HIT‐T15. Scanning electron microscopy revealed conspicuous shape changes of the microvilli following stimulation of these cells with bombesin or thapsigargin. These changes closely resemble those previously shown to accompany stimulation of hexose transport in adipocytes with insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 17 publications
(9 reference statements)
0
40
0
Order By: Relevance
“…Interestingly calcium released by IP3 stimulated higher secretion rates. These secretion rates are, however, similar to secretion rates in gonadotrophs (Tse, Tse, Almers & Hille, 1993) and pancreatic fl-cells (Ammala et al 1993) (Dunlop & Larkins, 1988), hepatocytes (Rossier, Bird & Putney, 1991), and insulin-secreting cells (Lange & Brandt, 1993) have suggested that some calcium stores are near the plasma membrane. The observation of IP3 receptors on secretory vesicles in chromaffin cells and insulin-secreting cells suggest an even more direct colocalization of calcium release sites with secretory vesicles (Yoo & Albanesi, 1990;Blondel et al 1994 Yamamoto et al (1987) had previously shown that the total amount of secretion could be increased maximally 2-fold with 2 JiM cAMP at about 4/M Ca!+ in electropermeabilized melanotrophs.…”
mentioning
confidence: 88%
“…Interestingly calcium released by IP3 stimulated higher secretion rates. These secretion rates are, however, similar to secretion rates in gonadotrophs (Tse, Tse, Almers & Hille, 1993) and pancreatic fl-cells (Ammala et al 1993) (Dunlop & Larkins, 1988), hepatocytes (Rossier, Bird & Putney, 1991), and insulin-secreting cells (Lange & Brandt, 1993) have suggested that some calcium stores are near the plasma membrane. The observation of IP3 receptors on secretory vesicles in chromaffin cells and insulin-secreting cells suggest an even more direct colocalization of calcium release sites with secretory vesicles (Yoo & Albanesi, 1990;Blondel et al 1994 Yamamoto et al (1987) had previously shown that the total amount of secretion could be increased maximally 2-fold with 2 JiM cAMP at about 4/M Ca!+ in electropermeabilized melanotrophs.…”
mentioning
confidence: 88%
“…Because of tighter binding of divalent cations to fixed charge centers, divalent cation conduction is more restricted. increases following receptor-mediated disorganization of the microvillar bundle structure (40,43,44).…”
Section: The F-actin Diffusion Barrier Is a Cation Exchangermentioning
confidence: 99%
“…Using a shearing protocol identical to that used for the preparation of glucose transporter-containing membrane fractions from adipocytes, Ca ϩϩ -storing vesicles were isolated from the surface of a hamster insulinoma cell line (HIT; Lange and Brandt, 1993a) and from hepatocytes . The Ca ϩϩ storage properties, the experimental conditions for ATP-dependent Ca ϩϩ uptake as well as the inhibitor spectrum of these vesicle fractions were identical to those of the microsomal systems from various cell types generally assigned to the endoplasmic/sarcoplasmic reticulum Ca ϩϩ ATPases.…”
Section: Hypothesis Of Microvillar Camentioning
confidence: 99%